Integrated actions of information and knowledge management in the accounting sector of a public university (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
It discusses the relevance of information and knowledge management in an institution of public higher education. It focuses on the stimulus, which can be implemented through assertive actions in the creation and maintenance of organizational knowledge, and as a general objective, analyzing the actions of the management of information and the knowledge of the technical coordination of Accounting and Finance of the University. In the methodological aspect, the research is characterized as study of case and field, configured as a study of qualitative and quantitative, exploratory and descriptive nature. It uses as a tool for data collection an individual questionnaire, without identification, which allowed us to recognize the actions of IKM, through the ‘diagnosis of knowledge management’, in the perspective of Bukowitz and Williams, adopted as a parameter. For the organization and analysis of data, the analysis of content was made. The results obtained reveal that the findings of the survey were positive for the shares of IKM, although there is a need for improvement with regard to encouraging the sharing of knowledge in the areas that make the Coordination of Accounting and Finance of the University. Keywords: Information Management. Knowledge Management. Information Science. Intellectual Capital. Organizational Knowledge. Link para o texto completo (PDF)http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/3122/2456